Urban identities: influences on socio-environmental values and spatial inter-relations - Cheshmehzangi, Ali; Heat, Tim (Elsevier B.V., 2012)
This research focuses upon the socio-environmental dimensions and urban identity of urban environments by evaluating human behaviours and space-to-human relations. In addition, approaches to urban re-branding will be analysed to evaluate the role of engineered identities in enhancing social integration. This particular study will focus upon the installation of temporary activities into the public realm and the impact that these can have upon perception, identity and activity within public spaces. A case study of temporary markets taking place in Nottingham’s Old Market Square in the UK will be evaluated to explore possibilities of maximising the potential of urban space.